Saldo Kas Minimal dan Optimalisasi Kas Pemerintah - Agung Mulyono (Jurnal Manajemen Perbendaharaan, 2021)
Cash minimum policy on General State of Cash Account or RKUN is aimed to fulfill cash needed for funding budget execution. That policy has possibility to be changed due to cash optimization purposes and advancement of banking technology. Study intend to increase our understanding about state cash management especially for cash balance on RKUN and explore a discourse in development of optimum cash management on RKUN for managing Government’s cost of fund. This paper uses simple average simulation, Boumol’s model dan Miller-Orr’s model with exploiting daily cash transaction on RKUN for 3 years to derive the form of the optimal cash balance under different assumptions about transaction costs and the demand for funds. Output of all models shows that amount of optimum cash on RKUN in the end of day should be smaller than the amount of cash set by cash minumun policy worth to Rp 2 billion. The result may open further discussion for policy changes on Government cash management.